2010
DOI: 10.3946/kjme.2010.22.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Cognitive and Learning Styles of Premedical Students

Abstract: In the visual (imagery)-verbal dimension, there was some correlation between cognitive and learning styles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Researchers hypothesize that a relation exists between the learning style and cognitive style. The outcomes of the existing research clearly shows that the information processing is linked to the preferred learning style of an individual (Ahn et al, 2010). Thus, the existing studies conclude that every individual has their own preferred learning style.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers hypothesize that a relation exists between the learning style and cognitive style. The outcomes of the existing research clearly shows that the information processing is linked to the preferred learning style of an individual (Ahn et al, 2010). Thus, the existing studies conclude that every individual has their own preferred learning style.…”
Section: Introductionmentioning
confidence: 99%
“…Data acquired from other published works (Fig. 3 ) have indicated that medical students have active, visual, sensing, and sequential LS priorities (except Nazarbayev and Taibah universities) [ 10 , 17 , 25 , 26 and 27 ]. Our clinical medical students’ learning styles were basically the same as those of the other medical students, but the active/reflective style was more balanced (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…According to the outcomes, students’ LS priorities were perceptual, sequential, and visual. Accordingly, as discussed in the literature, students majoring in the medical field prefer to master knowledge via demonstrations, photos, practice and familiarity with facts, diagrams, and algorithms sequentially and linearly [ 10 , 26 , 27 ]. Nevertheless, according to the analyses, no considerably significant differences were observed between priorities when continual active-reflective learning was a concern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mayer and Massa [6] suggested a standard that can differentiate learning style, cognitive style, and cognitive ability as follows: cognitive ability is an ability to do something; cognitive style involves a method that people use to process and represent information; and learning style refers to the style of information presentation that people prefer. Moreover, An et al [7] reported that there is a correlation between visual-verbal aspects of cognitive style and learning style. Summing up Mayer and Massa's and An et al's results, we can see that the type of information that a learner prefers is related to the way he/she processes and represents that information.…”
Section: Introductionmentioning
confidence: 99%